Variation for Quality of Pods in Prosopis Cineraria Mac Bride - Gupta, Ashok K; Solanki, K R; Kackar, N L (Annals of Arid Zone, 2016)
Qualitative attributes of Prosnpis cineraria pods viz. crude protein, reducing sugars and total sugar content varied from tree to tree as well as between widely separated provenances. In general, the extent of variability for these characters was more in arid regions as compared to semi-arid regions. Barmer region represented more than 30% coefficient of variation for all these characters.